Some nematodes, including two new species, from freshwater fishes in the Sudan and Ethiopia - Moravec, František; Scholz, Tomáš (Folia parasitologica, 2017)
Fourteen species (twelve adult and two larval) of nematodes belonging to the Ascaridoidea, Camallanoidea, Cosmocercoidea, Habronematoidea, Oxyuroidea, Seuratoidea and Trichinelloidea were collected from fishes in the Sudan (River Nile and Atbara Dam Lake), whereas only four species (one adult and three larval) of the Ascaridoidea, Camallanoidea, Dioctophymatoidea and Trichinelloideafrom fishes in Ethiopia (Lake Tana). The Sudanese material also contained two previously unknown species, Cucullanus mormyri sp. n. from Mormyrus caschive Linnaeus (type host), Mormyrus sp. and Marcusenius cyprinoides (Linnaeus) (all Mormyridae), and Procamallanus (Spirocamallanus) pseudospiralis sp. n. from Synodontis schall (Bloch et Schneider) (type host), S. frontosus Vaillant and S. nigrita Valenciennes (all Mochokidae), which are described based on light and scanning electron microscopical studies. Cucullanus baylisi Campana-Rouget, 1961, a little-known parasite of Synodontis spp., is redescribed in detail. A key to Procamallanus (Spirocamallanus) spp. from African inland fishes is provided. Falcaustra guiersi Vassiliadès, 1973 is considered a junior synonym of F. hexapapillata (Khalil, 1962). The findings represent several new host and geographical records. Cucullanus baylisi Lakshmi, 2000 (= a homonym to C. baylisi Campana-Rouget, 1961) is re-named as C. dubius nom. n. and is considered a species inquirenda.
Keywords: Nematode Infections; Animals; Nematoda; Female; ženské pohlaví; nemoci ryb; Sudan; nematodózy; Fish Diseases; Fishes; ryby; Fresh Water; hlístice; Male; sladká voda; Súdán; Ethiopia; zvířata; mužské pohlaví; Etiopie